The very hungry caterpillar - Carle, Eric (Great Britain Hamish Hamilton LTD, 1969)
This is the story of a very hungry caterpillar growing into a beautiful butterfly
Originally published: New York: World Publishing, 1969; London: Hamilton, 1970
Keywords: Caterpillars -- Pictorial works -- Juvenile fiction; Butterflies -- Metamorphosis -- Pictorial works -- Juvenile fiction; boardbooks; Children's stories -- Pictorial works